Measuring Health Literacy in Caregivers of Children: A Comparison of the Newest Vital Sign and S-TOFHLA. (November 2014) - Morrison, Andrea K.; Schapira, Marilyn M.; Hoffmann, Raymond G.; Brousseau, David C.
Objective . We examined the performance of the Newest Vital Sign (NVS) and the Short Test of Functional Health Literacy in Adults (S-TOFHLA) in caregivers of children. Method . Caregivers of children ≤12 years old seeking care for their child in a pediatric emergency department (ED) were tested using the NVS and the S-TOFHLA to measure health literacy. The results were compared with ED use outcomes. Result . The S-TOFHLA was found to have a ceiling effect as compared to the NVS; few caregivers scored in low literacy categories ( P < .0001). This finding was demonstrated in both lower ( P = .01) and higher ( P < .001) educational attainment groups. The NVS was predictive of ED use outcomes ( P = .02 and P < .01) whereas the S-TOFHLA was not ( P = .21 and P = .11). Conclusions . The measures do not seem to function similarly nor predict health outcomes equally. The NVS demonstrates sensitivity in identifying limited health literacy in younger adult populations.